Reporting adverse events in randomized controlled trials in periodontology: a systematic review - Faggion Junior, Clóvis Mariano; Tu, Yu-Kang; Giannakopoulos, Nikolaos Nikitas (Journal of clinical periodontology, 2013)
Background/Aims Reporting of adverse events is of paramount importance in randomized controlled trials (RCTs) to guide the implementation of new therapeutic approaches in clinical practice. The aim of this study was to assess the quality of adverse events reporting in RCTs published in the periodontal literature. Materials and Methods Two authors (CMF and NNG) searched the PubMed and LILACS electronic databases independently and in duplicate to identify RCTs published in periodontology from 2002 to 2003 and from 2011 to 2012. Reporting quality in RCTs was assessed with reference to the 2004 CONSORT Extension for Harms checklist. Differences in adverse events reporting between industry- and non-industry-funded RCTs were also determined. Cohen's kappa statistic was used to determine the extent of inter-reviewer agreement. Fischer's exact test was used to assess differences in reporting between the two samples. Results The analysis included 246 publications. One hundred twenty-four of 990 (13%) items and 223 of 1460 (15%) items were adequately reported in publications from 2002 to 2003 and from 2011 to 2012 respectively. Three checklist topics were significantly better reported in the 2011-2012 sample; two recommendations were better reported in non-industry-funded trials in publications from both periods. Conclusion Improvement and standardization of adverse events reporting in periodontology are needed.